TINJAUAN RELIGI ATAS MANUSIA DAN LINGKUNGAN - Yedi Purwanto (Jurnal Sosioteknologi, 2007)
Human as the God's most noble creature was appointed as the leader in the world. With his knowledge, man must understand his environment, and has a responsibility to take care of his living environment in line with Commandment of God in the Quran.